Clinical Use of PPARγ Ligands in Cancer. (17th December 2008) - Hatton, Jennifer L.; Yee, Lisa D.
Abstract : The role of PPARγ in adipocyte differentiation has fueled intense interest in the function of this steroid nuclear receptor for regulation of malignant cell growth and differentiation. Given the antiproliferative and differentiating effects of PPARγ ligands on liposarcoma cells, investigation of PPARγ expression and ligand activation in other solid tumors such as breast, colon, and prostate cancers ensued. The anticancer effects of PPARγ ligands in cell culture and rodent models of a multitude of tumor types suggest broad applicability of these agents to cancer therapy. This review focuses on the clinical use of PPARγ ligands, specifically the thiazolidinediones, for the treatment and prevention of cancer.